2018
DOI: 10.1001/jamanetworkopen.2018.0954
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood Geographic Spatial Factors With Rates of Childhood Obesity

Abstract: This study uses census block data in Arkansas to investigate spatial patterns in childhood obesity between the 2003-2004 and 2014-2015 academic years and to distinguish obesity risk attributable to social contagion vs neighborhood contextual factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…Given its high prevalence and severe impact on health outcomes, researchers had poured attention into the modifiable determinants and driving factors of childhood OW/OB. Several studies have found that childhood OW/OB is multifactorial and complex and is considered to result when various genetic, behavioural, environmental, physiological, social and cultural factors interact 13–16. It is increasingly recognised that where we live has an impact on our health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given its high prevalence and severe impact on health outcomes, researchers had poured attention into the modifiable determinants and driving factors of childhood OW/OB. Several studies have found that childhood OW/OB is multifactorial and complex and is considered to result when various genetic, behavioural, environmental, physiological, social and cultural factors interact 13–16. It is increasingly recognised that where we live has an impact on our health.…”
Section: Introductionmentioning
confidence: 99%
“…GIS has been employed in several innovative studies of OW/OB. For example, to explore regional variations and spatial clustering of obesity rates and to identify locations for targeted obesity intervention efforts 16 18 22–24. In addition, most of the previous analysis was conducted using large geographical units such as provincial or city level, making it difficult to provide effective implementation of local policies or decisions for obesity prevention.…”
Section: Introductionmentioning
confidence: 99%
“…At the neighborhood level, socioeconomic inequalities contribute to between-neighborhood differences in social and built environments, which impact obesity via more proximate factors (e.g., health behaviors; food markets; Schulz & Northridge 2004; Dubowitz et al, 2012; Inagami, Cohen, Brown, & Asch, 2009). A growing body of literature demonstrates several aspects of the socioeconomic, built, and social environment of a neighborhood contributes to unhealthy weight status during later childhood (Carroll-Scott et al, 2013; Fang, Thomsen, Nayga, & Goudie, 2018; Saelens et al, 2018), yet little is known about the effects of neighborhood disadvantage on children’s weight and potential proximate mediating factors during the earliest years of life.…”
mentioning
confidence: 99%
“…1,2 To better understand this trend, researchers have examined personal, family, institutional, community, and societal-level factors associated with greater risk for developing overweight and/or obesity in youth. 3,4 This research has shown that the prevalence of childhood obesity is unevenly distributed across geographic areas, 5,6 with higher rates in economically and socially deprived areas. [7][8][9] Furthermore, evidence indicates racial/ethnic and socioeconomic disparities in the extent to which adolescents' neighborhoods support physical activity 10 and access to food stores, restaurants, and healthy foods.…”
mentioning
confidence: 99%